1959
DOI: 10.1017/s0021859600020748
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physio-chemical studies on dwarf Herefords

Abstract: Thirty-six Hereford dwarfs, ‘comprest’, dwarf-like, and eight controls were available. Body and skin measurements were taken and the types of head abnormalities and cardiovascular activities were recorded. Haematological tests and chemical analysis of blood and hair were carried out.Typical dwarfs showed characteristic head abnormalities with varying degrees either at birth or later in life, possibly as a result of different stages of development at which the defective gene(s) comes into operation. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1960
1960
1970
1970

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Systematic studies on skin were not conducted, although Crenshaw et al (3) and Bone (1) assumed that the dwarfs possess thick skin. Hafez et al (8) observed that skins of dwarfs were thinner than those of normal animals.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies on skin were not conducted, although Crenshaw et al (3) and Bone (1) assumed that the dwarfs possess thick skin. Hafez et al (8) observed that skins of dwarfs were thinner than those of normal animals.…”
Section: Introductionmentioning
confidence: 99%